Locus of Control and Gender Influence on Relapse Avoidance Among Drug-Dependent Adolescents - Taiye Esther Omisola-Adebisi; Adebayo O. Adejumo; Uthman T. Jamiu; Dare A. Fagbenro; Timileyin M. Fashola (Universitas Negeri Surabaya, 2025)
Background: In Nigeria, few studies have investigated relapse avoidance ability and its antecedents among young adolescents. Objective: This study examined the role of locus of control and the influence of gender on relapse avoidance among adolescents undergoing treatment for substance use at the Federal Neuro-psychiatric Hospital, Yaba, Lagos State, Nigeria. Method: A cross-sectional survey design was employed to purposively select a sample of 344 adolescents (288 males and 56 females) using the adolescent relapse coping questionnaire and the Terry Pettijohn Locus of Control Scale for data collection. Results: Results indicated that Internal locus of control showed a positive effect (β = .17, p < .01), while external locus of control had a stronger influence (β = .25, p < .01) on relapse avoidance, together, they accounted for R²=.11%. No gender differences exist with relapse avoidance t(344) = -1.09 95% CI (-23.06, 6.61), p>.05). Conclusion: The study concluded that adolescents’ sense of control, rather than gender, plays a central role in relapse avoidance. Abstrak Latar Belakang: Di Nigeria, hanya sedikit penelitian yang telah meneliti kemampuan relapse avoidance ability dan faktor-faktor yang memengaruhinya di kalangan remaja muda. Tujuan: Penelitian ini menelaah peran locus of control dan pengaruh gender terhadap kemampuan menghindari kekambuhan pada remaja yang menjalani perawatan penyalahgunaan zat di salah satu rumah sakit, Yaba, Negara Bagian Lagos, Nigeria.Metode: Penelitian ini menggunakan desain cross-sectional survey design dengan teknik purposive sampling untuk memilih sampel sebanyak 344 remaja. Data dikumpulkan menggunakan Adolescent Relapse Coping Questionnaire dan Terry Pettijohn Locus of Control Scale. Hasil: Hasil penelitian menunjukkan bahwa internal locus of control memiliki pengaruh positif (β = .17, p < .01), sedangkan external locus of control memiliki pengaruh yang lebih kuat (β = .25, p < .01) terhadap kemampuan menghindari kekambuhan. Secara bersama-sama, kedua variabel tersebut menjelaskan R² = .11%. Tidak ditemukan perbedaan berdasarkan gender terhadap kemampuan menghindari kekambuhan t(344) = -1.09, 95% CI (-23.06, 6.61), p > .05. Kesimpulan: Sense of control pada remaja lebih berperan dibandingkan faktor gender dalam kemampuan menghindari kekambuhan.